Synthesis and Polymerization of Several New Maleimides Linked to Schiff Bases and Their Copolymers with Acrylonitrile - Al-Azzawi, Ahlam Marouf; Faiq, Esraa (Iraqi Journal of Science, 2021)
A series of new maleimide monomers substituted with Schiff base moieties were synthesized via acid-catalyzed condensation of 3-(N-maleimidyl)phenyl hydrazide with aromatic aldehydes and ketones. The newly synthesized monomers were introduced in free radical chain growth homopolymerization producing five new polymaleimides with pendent Schiff base moieties .The new monomers were introduced also in free radical chain growth copolymerization with acrylonitrile producing new five copolymaleimides containing pendent Schiff base moieties. The new homopolymers and copolymers are of great importance since incorporation of bulky Schiff base moieties in their repeating units exhibit them better solubility and processing properties which made them suitable for a variety of important applications.